1958
DOI: 10.1002/cber.19580910102
|View full text |Cite
|
Sign up to set email alerts
|

Die Thermolyse des Phenylazids in primären Aminen; die Konstitution des Dibenzamils

Abstract: Das von L. Wolff beim Zerfall des Phenylazids in Anilin erhaltene „Dibenzamil”︁ erweist sich als ungesättigtes Amidin mit siebengliedrigem Ring (IV oder V). Auch analoge Produkte aus Phenylazid und p‐Toluidin, p‐Phenetidin, N‐Methyl‐anilin, Benzylamin oder Cyclohexylamin sowie aus p‐Tolylazid und Anilin werden beschrieben. Ihre Konstitution zeigt, daß das zerfallende Arylazid den siebengliedrigen Ring bildet und das Arylamin in die Seitenkette eingeht. Die Acylierung von IV, nicht aber die Benzolsulfonylierung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…4). Characteristic bands of ACHT [19,[57][58][59]] could be clearly identified in the spectra of the irradiated matrix. Particularly noticeable is the band-mark associated with the intense antisymmetric stretching vibration of the ketenimine moiety (νC C N as.)…”
Section: Uv-irradiation Experiments (λ > 235 Nm)mentioning
confidence: 99%
“…4). Characteristic bands of ACHT [19,[57][58][59]] could be clearly identified in the spectra of the irradiated matrix. Particularly noticeable is the band-mark associated with the intense antisymmetric stretching vibration of the ketenimine moiety (νC C N as.)…”
Section: Uv-irradiation Experiments (λ > 235 Nm)mentioning
confidence: 99%
“…The nature of this ring expansion has been under debate for several years. Huisgen and Vossius [16] suggested that the first intermediate formed from the singlet phenyl nitrene 2 was the bicyclic azirine 5. However, later IR spectroscopic studies [17] on the photochemistry of matrix isolated phenyl azide gave evidence of the formation of the didehydroazepine 4.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the investigations of Huisgen et al [55] are of greater significance in this connection. Thermolysis of phenyl azide in aniline yielded a monocyclic isomer of azepine, the cyclic amidine or azatropilidene derivative (69) [*I.…”
Section: Heterotropilidenesmentioning
confidence: 88%
“…Further investigations of the fine structure and reactivity in these octet systems are necessary in order to recognize similarities to and differences from the corresponding tropylium cations. So far only several mono-, di-, and tribenzo derivatives of the three heterotropilidenes (61) to (63) have been prepared as well as some polysubstituted derivatives stabilized by additional opportunities for resonance, and various dihydro derivatives [54,55]. Only limited conclusions are permissible from the chemical and physical behavior of the benzoheterotropilidenes (65) studied by Dimroth and Freyscldag [54] concerning the properties of the hypothetical monocyclic compounds (61) to (63), because in the bicyclic derivatives (65) stabilization of the benzene moiety by its electron sextet presumably far outweighs any stabilization of the heterocyclic 7-membered ring.…”
Section: Heterotropilidenesmentioning
confidence: 99%
See 1 more Smart Citation